Penggunaan Media Sosial Baharu: Isu-isu Dan Panduan Perspektif Islam - Syed Mohammad Hilmi Syed Abdul Rahman; Mohd Anuar Ramli; Che Zarrina Sa'ar; Azah Anir Norman; Muhammad Hazim Mohd Azhar; Mohd Anuar Mamat (Akademi Pengajian Islam, Universiti Malaya, 2024)
Vol. 50 No. 1